Half Cycle Discrete Transformation for Voltage Sag Improvement in an Islanded Microgrid using Dynamic Voltage Restorer - N.S. Srivatchan; P. Rangarajan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Growing demand for clean and green power has increased penetration of renewable energy sources into microgrid. Based on the demand supply, microgrid can be operated in grid connected mode and islanded mode. Intermittent nature of renewable energy sources such as solar and wind has lead to number of control challenges in both modes of operation. Especially islanded microgrid throws power quality issues such as sag, swell, harmonics and flicker. Since medical equipments, semiconductor factory automations are very sensitive to voltage variations and therefore voltage sag in an islanded microgrid is of key significance. This paper proposes a half cycle discrete transformation (HCDT) technique for fast detection of voltage sag in an islanded microgrid and thereby provides fast control action using dynamic voltage restorer (DVR) to safe guard the voltage sensitive equipments in an islanded microgrid.  The detailed analysis of simulation results has clearly demonstrated the effectiveness of proposed method detects the voltage sag in 0.04 sec and there by improves the voltage profile of islanded microgrid.